PGPR, PEMUPUKAN AN ORGANIK DAN VERMIKOMPOST TERHADAP PANJANG BATANG & DIAMETER TEBU (Saccharum officinarum L.) DI SCREENHOUSE - Pitaloka, Dyah; Sudiarso, Sudiarso; Yudo Tyasmoro, Setyono; Prayogo, Cahyo (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2021)
Combine between fertilizer vermicompos, inorganic fertilizer and PGPR is a breakthrough in the development of agricultural technology to increase the growth of persistent vegetative state and the results of production plant cane. This researsh aims to determine the effect of a combination of organic fertilizers (vermicompost), inorganic and PGPR on the growth of the length and diameter of plant cane. Vegetative growth studycondukted in screenhouse Brawijaya university poor starts in August 2019 until january 2020. Treatment such as 1). PGPR 5 ml per liter or 10 ml per liter combined with fertilizer inorganic 100% (7 kw ZA + 3 kw SP 36 + 3 kw kcl 2). PGPR 5ml per liter or 10 ml per liter combined with vermikompos 10 ton/ha mixed with 50% inorganic fertilizer the research was compiled using random design comlplete factorial. Repeated three times result showing that the PGPR 10 ml per liter proved to be able to increase long stalks of, the provision of a mixture of fertilizer and inorganic vermikompos 50% able to ancrease growth of plant in the trunk dameter, sugar cane, a combination pgpr and vermikompos mixed inorganic fertilizers able to enlarge the diameter of a plant stem sugar cane.